Forces Acting on Submillimeter Spheres at the Air-Water Interface - 王乐锋 刘路 徐慧超 荣伟彬 孙立宁 (Chinese physics letters, 2015)
The forces acting on submillimeter spheres at the air-water interface are investigated theoretically and experimentally. To calculate the capillary force acting on the sphere, an iterative method is used to determine the immersing position of the liquid interface on the sphere for a given distance. Then the total forces acting on the sphere are considered. The scaling effects of the net force acting on the sphere at the air-water interface are demonstrated. For the experiments, the force-position relationship of microspheres is measured with a precise electronic balance. The results show that the evaporation of the liquid in the container affects the measuring results greatly under ambient conditions. After considering the evaporation compensation, there is a great agree- ment between the theoretical and experimental results. Obvious hysteresis phenomena of the force-distance curve during the emersion processes are also observed and explained.